(untitled) (Journal of the College of Basic Education, 2023)
The living reality of the human being was not fully consistent with the aspirations of the great beings; lost The struggle for survival between man and his surroundings has intensified since his formative dispersal over the globe. . It is natural for a person to look for ways to liberate himself from perpetuating fear in himself. so His self-image worsened until it turned into a psycho-social disease that dominated the folds of perceptions.